Effective thermoelectric properties with polyselenophene/CuxS x S composites - Huner, Azra (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
In this study, polyselenophene (PSe), which has more raw materials, lower cost, and can be processed more easily than inorganic thermoelectric materials, was synthesized as a polymeric thermoelectric material with a simple method by chemical oxidative polymerization in aqueous medium. Copper sulfide (CuxS) x S) was synthesized and taken from it in different ratios compared to PSe, PSe/CuxS x S composites were prepared. The Seebeck coefficient of PSe is 160 mu VK-1,- 1 , while that of PSe/CuxS x S composite containing 30% CuxS x S is 410 mu VK-1.- 1 . The PSe/CuxS3 x S3 composite with 30% CuxS x S had the highest Seebeck coefficient and power factor, measuring 410 mu VK-1- 1 and 5043 mu Wm- 1K- K- 2 , respectively. The electrical conductivity of PSe and PSe/CuxS x S composites obtained in this study is relatively high, ranging from 10 to 405 Scm-- 1 . PSe and its composites were characterized by FTIR, UV-Vis., XRD, TGA, EDX, and FESEM.
Keywords: Clean energy; Seebeck coefficient; Thermoelectric; Conducting polymers; Composites; FILMS; POWER; SELENOPHENE; PERFORMANCE; COPOLYMERS; Chemistry; Physics